Willingness to pay for Tipolog-Tamugan watershed rehabilitation and protection domestic perspective - Astronomo, Ivi Jaquelyn T. (School of Management, University of the Philippines Mindanao, 2016)
Water is very essential for survival but less than 1% of the freshwater stored in underground and surface watersheds are accessible for human consumption. Davao City Water District (DCWD) has observed the increasing water demand in the city due to population and urban growth. As such, DCWD are rendering efforts to avoid over-extraction of groundwater which may lead to land subsidence, drying up of wells, and saltwater intrusion. Tipolog-Tamugan surface water is the prospective alternative source and DCWD has also thought of a watershed rehabilitation and protection program for its watershed. This research aims to determine the water utilization patterns of households connected to DCWD, analyze their level of environmental awareness, and estimate their willingness to pay for the watershed rehabilitation and protection program using the contingent valuation method. Using a household survey instrument, 400 respondents from different barangays in Davao City were interviewed. Results shows that the mean willingness to pay differs between people who value the watershed and not; and between levels of certainty. Including protest vote, the mean WTP is P130.69 for ?1to10? level of certainty and P37.23 for ?7to10? level of certainty. Excluding protest votes, the mean WTP is P253.33 for ?to10? rate of certainty while P76.76 for ?7to10? rate of certainty. These findings suggest that households in Davao City are willing to pay a considerable amount for the watershed rehabilitation and protection program and their WTP can be increased with significant efforts geared towards increasing environmental awareness and concern.